Normothermic human kidney preservation drives iron accumulation and ferroptosis - Marlon J. A. de Haan; Marleen E. Jacobs; Annemarie M. A. de Graaf; Roan H. van Scheppingen; Rico J. E. Derks; Dorottya K. de Vries; Jesper Kers; Ian P. J. Alwayn; Cees van Kooten; Elena Sánchez-López; Martin Giera; Marten A. Engelse; et al. (Nature Communications)
Abstract Ex vivo normothermic machine perfusion has been proposed to protect deceased donor kidneys. However, its benefits remain ambiguous. We postulate that the use of red blood cells (RBCs) and associated secondary hemolysis may in fact cause renal injury, offsetting potential advantages. During 48-hour normothermic perfusion of seven human donor kidneys, we observed progressive hemolysis, leading to iron accumulation in perfusate and tissue. Untargeted lipidomic profiling revealed significant increases in oxidized phospholipid species in perfused kidneys, pointing towards iron-dependent cell death known as ferroptosis. Next, in twelve additional perfusions, we assessed strategies to mitigate hemolysis-driven injury. Dialysis-based free hemoglobin removal reduced lipid peroxidation, but a ferroptosis gene signature persisted. In contrast, cell-free perfusion at subnormothermia negated iron accumulation, the ferroptosis gene signature, phospholipid peroxidation, and acute kidney injury. Our findings highlight the pathological role of hemolysis and iron on the kidney, urging restraint in the clinical application of RBC-based kidney perfusion.